Apocynin alleviates cisplatin-induced testicular cytotoxicity by regulating oxidative stress and apoptosis in rats - ERCAN, FERİHA; ŞENER, GÖKSEL (WILEY, 2019)
The aim of this study was to investigate possible protective effects of apocynin (APO), an NADPH oxidase (NOX2) inhibitor, on cisplatin (CIS)-induced testicular damage. Four groups of Sprague Dawley rats were used: control, APO, CIS and CIS+APO. Following a single intraperitoneal dose of CIS (7 mg/kg), either dimethyl sulfoxide or APO (25 mg/kg) was administered orally for 5 days. Testis samples were evaluated microscopically for general histopathology and ultrastructure, proliferating and apoptotic cells, and NOX2 localization. Sperm parameters were evaluated. Malondialdehyde (MDA) and glutathione (GSH) levels and superoxide dismutase (SOD), myeloperoxidase (MPO) and 8-hydroxy-2-deoxyguanosine (8-OHdG) activities were analysed biochemically. The CIS group had a greater number of abnormal spermatozoa, atrophic seminiferous tubules, apoptotic and NOX2-immunoreactive cells; numerous large vacuole formations in the cytoplasm of germinal epithelial cells; degenerated intercellular tight junctions; higher MDA, 8-OHdG and MPO levels; decreased numbers of spermatozoa; and lower proliferative index and GSH and SOD levels. All these histologic and biochemical results were better in the CIS+APO group. CIS causes testicular damage by decreasing spermatogenic cell lines and increasing NOX2 activity and apoptosis through oxidative stress. APO prevents testicular damage, possibly by its antioxidant effects.
Keywords: apocynin; apoptosis; cisplatin; NOX2; testis; ENDOPLASMIC-RETICULUM STRESS; CELL-DEATH; THIAMINE PYROPHOSPHATE; PROTECTIVE ROLE; CANCER CELLS; DNA-DAMAGE; MICE; CARDIOTOXICITY; INHIBITION; PARAMETERS